Pengaruh Penggunaan Teknologi Informasi Terhadap Pelayanan Administrasi Sekolah di SLTA dan Madrasah - Sundari, Gita; Rusdinal; Sulastri; Yulianto Santoso (Global Action and Education for Society, 2024)
This research aims to obtain information about the use of information technology and school administrative services, as well as the impact of information technology use on school administrative services. The hypothesis proposed in this study is